Design methodology for in situ cold recycled mixtures with emulsion and 100% rap. (20th August 2019) - Flores, Guillermo; Gallego, Juan; Miranda, Lucía; Marcobal, José Ramón
Graphical abstract: Highlights: The development of a new methodology of design of cold recycled mixtures with emulsion is developed. The evaluation of the mixture is based on its volumetric and mechanical properties. A Global Performance Index is proposed to compare the formula and optimize the mixture. Abstract: At present there is no consensus on the most suitable methodology for the design of cold recycled mixtures with emulsion, due to its complexity. Therefore, design is generally based on compliance with one or more volumetric or mechanical parameters established in the highway regulations, which does not guarantee the optimization of the mixture. The present work proposes a design methodology for cold recycled mixtures with emulsion, in which 6 parameters are evaluated: Air voids, Indirect Tensile Stress, Indirect Tensile Strength Ratio, Wheel Tracking, Stiffness Modulus and Fatigue life. Performance indexes were established to evaluate the values obtained from the tests according to behavior graphs with the maximum value of 1. These graphs evaluate the results of the tests, considering as a maximum value the most favorable results for the optimal performance of the mixture. Finally, for the analysis of the mixtures the authors propose a Global Performance Index (GPI) that shows the average of the 6 parameters measured. The result is a number that represents each job mix formula, which is sensitive to changes in the values of the properties and is obtained using a systematic methodology. Therefore, the choice is based on technical criteria and according with the GPI; the influence of the materials or the formulas used for each mixture can be ranked.